Impact of community-driven interventions on dietary and physical activity outcomes among a cohort of adults in a rural Appalachian county in Eastern Kentucky, 2019–2022 - Norman-Burgdolf, Heather; DeWitt, Emily; Gillespie, Rachel; Cardarelli, Kathryn M.; Slone, Stacey; Gustafson, Alison (Frontiers in Public Health, 2023)
Several environmental level factors exacerbate poor health outcomes in rural populations in the United States, such as lack of access to healthy food and locations to be physically active, which support healthy choices at the individual level. Thus, utilizing innovative place-based approaches in rural locations is essential to improve health outcomes. Leveraging community assets, like Cooperative Extension, is a novel strategy for implementing community-driven interventions. This prospective cohort study (n=152), recruited in 2019 and surveyed again in 2020 and 2021, examined individual level changes in diet and physical activity in one rural Appalachian county. During this time, multiple community-driven interventions were implemented alongside Cooperative Extension and several community partners. Across the three-year study, the cohort indicated increases in other vegetables and water and reductions in fruits and legumes. There were also reductions in less healthy items such as French fries and sugar-sweetened beverages. The cohort also reported being less likely to engage in physical activity. Our findings suggest that key community-driven programs may have indirect effects on dietary and physical activity choices over time. Outcomes from this study are relevant for public health practitioners and community organizations working within rural Appalachian communities to address health-related behaviors.